Microstructure and mechanical properties of aluminum-steel dissimilar metal welded using arc and friction stir hybrid welding - Liu, Ji; Wu, Bintao; Wang, Ziran; Li, Chunwang; Chen, Guangyu; Miao, Yugang (Elsevier, 2023)
In this study, arc and friction stir hybrid welding (AFSHW) was proposed to weld aluminum-steel dissimilar metals in attempt to realize high quality joining. Firstly, an interlayer was produced on galvanized steel by using bypass current-metal inert gas welding (BC-MIG), and then an aluminium plate was jointed via Friction stir lap welding (FSLW). The effects of tool pin length and FSLW times on the microstructure and mechanical properties of dissimilar joints were fully investigated by means of Optical Microscopy (OM), Scanning Electron Microscope (SEM), Electron Backscatter Diffraction (EBSD), and mechanical testing. The results show that as pin length increased, joint strength tended to increase and then decrease, and the tensile failure partially occurred at aluminium base metal. However, with additional number of FSLW, joint strength would be reduced, which was attributed to attenuated dislocation density and strain concertation in dissimilar joint. The research outcomes will provide a new welding method to obtain sound Al-Fe dissimilar metal joint, and benefit to a better understanding of Al-Fe joining mechanism.
Keywords: AFSW; Aluminum-steel joint; Interfacial microstructure; Mechanical strength